Design and Analysis of High Performance Home Solar Energy System. - I. Al-Mashhadany, Yousif (Anbar Journal of Engineering Sciences, 2012)
Rising energy prices and growing environmental concerns are making solar electric systems more attractive to homeowners. A solar electric system reduces high energy costs and keeps your home up and running during power out-ages. The advantages to buying a solar electric system include: Saving a significant amount on your electric bill. Increasing your home’s appraisal value. Enjoying reliable, clean, free power for 25 to 30 years. Helping and assist to boost our economy by creating jobs and new solar companies. A solar electric system is typically made up of solar panels, an inverter, battery, charge controller, wiring, and support structure. The three most common types of solar electric systems are grid-connected, grid-connected with battery backup, and off-grid (stand-alone). This work presents design and analysis of high performance of home solar energy, that include: the orientation and pitch of the south‌ernmost facing roof to maximize solar gain, the roof vents, chimneys, gables or other obstructions in order to sit to the north side of the planned array. Ensure that the roof structure is strong enough. Structural support into the roof to handle the weight of a rack-mounted system. The space for inverters and disconnects near the main service panel. Finally comparison between these systems with other sources of energy.